Detection of the Bovine Leptin Gene rs29004488 Polymorphism by Introducing a New Restriction Enzyme Site For PCR-RFLP - GURSES, Murad; BAYRAKTAR, Metin; YUCE, Huseyin; ONALAN , Ebru (MAS Journal of Applied Sciences, 2023)
Leptin is a hormone mainly synthesized in adipose tissue and plays an important role in the regulation of appetite, energy metabolism, body weight and reproductive functions. The rs29004488 polymorphism in the 2nd exon of the bovine leptin gene, which results in an amino acid change from arginine to cysteine, has been reported to be associated with economically important traits such as growth, carcass traits, milk yield and reproduction. In cattle, the leptin gene rs29004488 polymorphism can be detected by PCR-RFLP method using Kpn2I enzyme. However, this method has some limitations in terms of primer degradation. In this study, a new PCR-RFLP method was investigated to detect rs29004488 polymorphism of leptin gene in cattle. Using the created restriction site PCR (CRS-PCR) method, PstI enzyme recognition site was introduced into the PCR products, and rs29004488 polymorphism was successfully detected using newly designed primers and PstI enzyme. The obtained results were confirmed by DNA sequence analysis and comparison with Kpn2I enzyme cleavage results. This study demonstrates that the rs29004488 polymorphism can be detected by an efficient and low-cost method using CRS-PCR-RFLP and PstI enzyme.